Gene silencing mechanisms mediated by Aubergine-piRNA complexes in Drosophila male gonad. - Nishida, K.M.; Saito, K.; Mori, T.; Kawamura, Y.; Nagami-Okada, T.; Inagaki, S.; Siomi, H.; Siomi, M.C. (RNA (New York, N.Y.), 2007)
Genetic studies have shown that Aubergine (Aub), one of the Piwi subfamily of Argonautes in Drosophila, is essential for germ cell formation and maintaining fertility. aub mutations lead to the accumulation of retrotransposons in ovaries and testes, and Stellate transcripts in testes. Aub in ovaries associates with a variety of Piwi-interacting RNAs (piRNAs) derived from repetitive intergenic elements including retrotransposons. Here we found that Aub in testes also associates with various kinds of piRNAs. Although in ovaries Aub-associated piRNA populations are quite diverse, piRNAs with Aub in testes show a strong bias. The most abundant piRNAs were those corresponding to antisense transcripts of Suppressor of Stellate [Su(Ste)] genes known to be involved in Stellate gene silencing. The second most abundant class was made up of those from chromosome X and showed strong complementarity to vasa transcripts. Immunopurified Aub-piRNA complexes from testes displayed activity in cleaving target RNA containing sequences complementary to Stellate and vasa transcripts. These results provide the first biochemical insights into gene silencing mechanisms mediated by Aub and piRNAs in fly testes.